2022
DOI: 10.3390/appliedchem2020003
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Soaking and Sprouting on the Physicochemical Characteristics of Tigernut Tubers (Cyperus esculentus L.)

Abstract: The influence of soaking and germination on the physicochemical characteristics of tigernut tubers (Cyperus esculentus L.) are investigated. Tubers (Ø > 1 cm) were soaked in an ascorbic acid solution (0.1%) for 48 h at 40 °C before undergoing germination for 6 days. The textural profile, the capacity and germination energy and the biochemical composition of these tubers were determined. The germination energy varied from 76.18 to 79.48% for the quantities of solution of 24 and 48 mL, respectively. The textu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 30 publications
1
8
2
Order By: Relevance
“…The soluble sugar content of the freshly harvested, native TNs was 11.94 ± 0.31 • Bx, which increased to 34.38 ± 2.39 • Bx (Figure 2) after the drying period and milling process, confirming that the temperature and exposure period contribute to the accumulation of sugar in TNs (Kizzie-Hayford, Dabie, et al, 2021). The sproutingrelated decrease of the sugar content of TN in this study is contradictory to the increase shown by Djomdi et al (2022). This disparity can be partly attributed to the state of the TN prior to sprouting: On the one hand, freshly harvested TN shows a low sugar content (Kizzie-Hayford, Dabie , et al, 2021), and the amylase activity is reported to be minimal between 30 and 40 • C (Avwioroko et al, 2019), being comparable to the sprouting temperature.…”
Section: Effects Of Sprouting On the Nutrient Contentcontrasting
confidence: 57%
See 4 more Smart Citations
“…The soluble sugar content of the freshly harvested, native TNs was 11.94 ± 0.31 • Bx, which increased to 34.38 ± 2.39 • Bx (Figure 2) after the drying period and milling process, confirming that the temperature and exposure period contribute to the accumulation of sugar in TNs (Kizzie-Hayford, Dabie, et al, 2021). The sproutingrelated decrease of the sugar content of TN in this study is contradictory to the increase shown by Djomdi et al (2022). This disparity can be partly attributed to the state of the TN prior to sprouting: On the one hand, freshly harvested TN shows a low sugar content (Kizzie-Hayford, Dabie , et al, 2021), and the amylase activity is reported to be minimal between 30 and 40 • C (Avwioroko et al, 2019), being comparable to the sprouting temperature.…”
Section: Effects Of Sprouting On the Nutrient Contentcontrasting
confidence: 57%
“…Shoots of sprouted TNs (Figure 1) were visually detectable after 3 days of incubation. The fraction of sprouted tubers after 3 days was 78% ± 4.5%, which is in the upper level of the range (0%-75%) reported in literature (Djomdi et al, 2022). TNs are sometimes treated with hydrogen peroxide, ascorbic acid (Djomdi et al, 2022), or sodium hypochlorite (Okoye & Eni, 2018) to disinfect and prevent fungal growth during sprouting, and both the concentration and the type of disinfectant may affect sprouting efficiency (Tornuk et al, 2011).…”
Section: Effects Of Sprouting On the Nutrient Contentmentioning
confidence: 79%
See 3 more Smart Citations